Role of perceived risks to tourists in building their future intention: a conceptual model - Altarawneh, Wazerah, S.; Omar, Hamimi; Tahir, Shaharuddin (2018)
Tourism is vital to the economy of a country. Successful tourism marketing strategies require an understanding of why people travel and what factors influence their behavioural intention of choosing a travel destination. Tourism scholars have recognized the impact of perceived risk on travel behaviour and decision, because tourists are likely to avoid destinations with greater perceived risk regardless of whether that notion is a real representation of the level of safety in a destination. While overall the field of tourism has been abundantly researched, there are certain areas where there is a paucity of research such marketing strategies of destinations that sorted by tourists as a risky destination. This article contributes to this extremely important researched subject, specifically, this study seeking to investigate the role of perceived risks in building the tourists future intentions toward the destination. The research is focusing on developing a conceptual model which identifies the components of the tourist behaviour that corresponding to the three stages, namely, perceived risks stage, actual experience stage, and future intention stage